Answer:
![\bold{1.\quad y=-(1)/(2)(x-9)^2+10}](https://img.qammunity.org/2021/formulas/mathematics/high-school/m4grk57iob01lzucbkrk4lvoo7dc0hz01v.png)
2. x = (y - 1)² + 4
![\bold{3.\quad x=(1)/(2)(y-2)^2+7}](https://img.qammunity.org/2021/formulas/mathematics/high-school/evfiwe66e56ziipyxemo8s27g9d3mv6fxe.png)
Explanation:
Notes: The vertex form of a parabola is y = a(x - h)² + k or x = a(y - k)² + h
- (h, k) is the vertex
- p is the distance from the vertex to the focus
![\bullet\quad a=(1)/(4p)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4pfcb33ipla9jfgz8nv24e6qd6gqmzx2b9.png)
1)
![\text{Vertex}=(9, 10)\qquad \text{Focus}=\bigg(9,(19)/(2)\bigg)\\\\\text{Given}:(h, k)=(9, 10)\\\\\\p=focus-vertex=(19)/(2)-(20)/(2)=(-1)/(2)\\\\\\a=(1)/(4p)=(1)/(4((-1)/(2)))=(1)/(-2)=-(1)/(2)\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/2iddpeyfaumqp31x7ooyz03dksyjh78clu.png)
Now input a = -1/2 and (h, k) = (9, 10) into the equation y = a(x - h)² + k
![\bold{y=-(1)/(2)(x-9)^2+10}](https://img.qammunity.org/2021/formulas/mathematics/high-school/odmzw1yknbwkuom538m4mxmo7m3vcchvn1.png)
*****************************************************************************************
2)
![\text{Vertex}=(4, 1)\qquad \text{Focus}=\bigg((17)/(4),1\bigg)\\\\\text{Given}:(h, k)=(4, 1)\\\\\\p=focus-vertex=(17)/(4)-(16)/(4)=(1)/(4)\\\\\\a=(1)/(4p)=(1)/(4((1)/(4)))=(1)/(1)=1\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/r3ouninmhqabj25pvhe7edbl0ry0apq3wr.png)
Now input a = 1 and (h, k) = (4, 1) into the equation x = a(y - k)² + h
x = 1(y - 1)² + 4 → x = (y - 1)² + 4
*****************************************************************************************
3)
![\text{Vertex}=(7, 2)\qquad \text{Focus}=\bigg((15)/(2),2\bigg)\\\\\text{Given}:(h, k)=(7, 2)\\\\\\p=focus-vertex=(15)/(2)-(14)/(2)=(1)/(2)\\\\\\a=(1)/(4p)=(1)/(4((1)/(2)))=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/qdhacfbi60tb2698zd3zjyhas2sgipqxc6.png)
Now input a = 1/2 and (h, k) = (7, 2) into the equation x = a(y - k)² + h
![\bold{x=(1)/(2)(y-2)^2+7}](https://img.qammunity.org/2021/formulas/mathematics/high-school/4xzht8ljmu8m4qqyh4p5m2ubvalgw7hw33.png)